Ferroptosis-related genes as diagnostic markers for major depressive disorder and their correlations with immune infiltration - Chen, Jingjing; Jiang, Xiaolong; Gao, Xin; Wu, Wen; Gu, Zhengsheng; Yin, Ge; Sun, Rui; Li, Jiasi; Wang, Ruoru; Zhang, Hailing; Du, Bingying; Bi, Xiaoying (Frontiers in Medicine, 2023)
Background: Major depression disorder (MDD) is a devastating neuropsychiatric disease, and one of the leading causes of suicide. Ferroptosis, an iron-dependent form of regulated cell death, plays a pivotal role in numerous diseases. The study aimed to construct and validate a gene signature for diagnosing MDD based on ferroptosis-related genes (FRGs) and further explore the biological functions of these genes in MDD.The datasets were downloaded from the Gene Expression Omnibus (GEO) database and FRGs were obtained from the FerrDb database and other literatures. Least absolute shrinkage and selection operator (LASSO) regression and stepwise logistic regression were performed to develop a gene signature. Receiver operating characteristic (ROC) curves were utilized to assess the diagnostic power of the signature. GO enrichment analysis was used to explore the biological roles of these diagnostic genes, and ssGSEA algorithm was used to evaluate immune infiltration in MDD. Animal model of depression was constructed to validate the expression of the key genes.Results: Eleven differentially expressed FRGs were identified in MDD patients compared with healthy controls. A signature of three ferroptosis-related genes (ALOX15B, RPLP0 and HP) was constructed for diagnosis of MDD. Afterwards, ROC analysis confirmed the signature's discriminative capacity (AUC= 0.783, 95% CI= 0.719-0.848). GO enrichment analysis revealed that the differentially expressed genes (DEGs) related to these three FRGs were mainly involved in immune response. Furthermore, spearman correlation analysis demonstrated that these three FRGs were associated with infiltrating immune cells. ALOX15B and HP were significantly upregulated and RPLP0 was significantly downregulated in peripheral blood of the LPS-induced depressive model.Our results suggest that the novel ferroptosis-related gene signature had a good diagnostic performance for MDD, and these three FRGs correlated with immune infiltration in MDD.